The methodology of straightening the land plot boundary in the course of land consolidation - Malashevskyi, Mykola; Malashevska, Olena (Geodesy and Cartography, 2024)
The issue of land plot boundary straightening in the course of land consolidation has been examined in the study. Over the course of buying out and swapping, adjacent land plots are being incorporated into one land tenure. However, the land plots are inconvenient for cultivation due to broken boundaries. Measures on the boundary straightening comply with the demands of landowners at voluntary land consolidation, when they are interested in the least possible alteration of the boundaries of the existing land plots. The study aims at the substantiation of the methodology for the straightening of land plot boundary with the help of the peer exchange of their parts. Preconditions for the formation of broken boundaries in the course of land consolidation have been scrutinized. Algorithms for land plot boundary straightening with the help of the exchange of the parts of peer land plots have been suggested. The calculation of typical cases of broken boundary straightening has been suggested. The boundary straightening methodology has been tested in a land mass in Kyiv Region, Ukraine. The results of the research can be used in the course of voluntary land consolidation, at the developing of preliminary land reallotment plan for agricultural and built-up land.